Sexual Harassment Survivor's Self Disclosure in Twitter - Pertiwi, Anisa Yuliana; Palupi, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: Word word word word word word word word word word word word word word word word word word word word Purpose : The purpose of this qualitative study is to investigate how survivors of sexual harassment manage their privacy when disclosing their stories on Twitter, using Communication Privacy Management (CPM) theory. Methodology : This study collected data through interviews and observations, and analyzed it using Miles and Huberman's technique, while employing source triangulation to ensure data validity. Results: The results revealed that the informants in the study employed privacy management techniques when disclosing their stories on Twitter, such as restricting private information and avoiding revealing the identity of the perpetrator. The survivors controlled information ownership by double-checking their stories before sharing them, and paying attention to the wording, sentence structure, and language used. Applications/Originality/Value: The study also identified two perceived criterias for rule management: risk-benefit and dialectical tension. These factors influenced the survivors' decisions to disclose their experiences of sexual harassment, with some individuals feeling more comfortable sharing their experiences than others.